Concurrence of Rheumatoid Arthritis and Ankylosing Spondylitis: Analysis of Seven Cases and Literature Review - Flores-Robles, Bryan-Josué; Labrador-Sánchez, Eztizen; Andrés-Trasahedo, Estíbaliz; Pinillos-Aransay, Valvanera; Joven-Zapata, María-Yasmina; Torrecilla Lerena, Laura; Salazar-Asencio, Osman-Alberto; López-Martín, Juan-Antonio (Case Reports in Rheumatology, 2022)
Introduction. The association of rheumatoid arthritis (RA) and ankylosing spondylitis (AS) in a single patient is a rarely described phenomenon. AS and RA are conditions that can have a high impact on the morbidity and mortality of patients. Methods. We described the clinical, epidemiological, analytical, and radiological characteristics of 81 patients with concomitant diagnosis of rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Of these patients, seven were diagnosed at our hospital. A literature review was carried out using Medline, Embase, Scopus, and virtual hospital libraries, including the period from January 1950 to April 2020. Results. Regarding the results, 71% of the patients were men, with a mean age of 53 years (±14.83). RA was the first disease diagnosed in 52% of the cases. Approximately 53% of the patients had rheumatoid nodules, and 83% reported inflammatory lumbar pain during their evaluation. Erosions were observed on radiographs of the hands and/or feet in 85% of the cases, and almost all the patients (80/81) had sacroiliitis on imaging studies. Approximately 92% of the cases were rheumatoid factor (RF) positive and 90% HLA B-27 positive. Conclusions. The coexistence of RA and AS is highly uncommon. With the data obtained in this review, it seems that there exist erosive radiological patterns, positivity for RF, involvement of the axial skeleton, and rheumatoid nodules at a higher frequency than those patients with a single diagnosis of the two entities. More data are needed to corroborate this association.